Neuroprotective and anti-inflammatory properties of a novel non-thiazolidinedione PPARγ agonist in vitro and in MPTP-treated mice. (27th August 2015) - Lecca, D.; Nevin, D.K.; Mulas, G.; Casu, M.A.; Diana, A.; Rossi, D.; Sacchetti, G.; Carta, A.R.
Highlights: MDG548 is a novel highly selective PPAR-gamma agonist. MDG548 is protective against H2 O2 and MPP+ in cultured neurons. MDG548 inhibits NF-kB activation in vitro . MDG548 is neuroprotective in a MPTP model of PD. MDG548 counteracts microglia reactivity and iNOS in the MPTP model. Abstract: Peroxisome proliferator-activated receptor (PPAR)γ is a potential pharmacological target for disease-modification in Parkinson's disease (PD), mainly acting by modulating the neuroinflammatory response. However, currently available agonists thiazolidinediones (TZDs) present limitations due to safety concerns. We evaluated a novel thiobarbituric-like compound MDG548, which acts as a functional PPARγ agonist displaying higher and selective binding affinity as compared to TZDs. Neuroprotection by MDG548 was tested in vitro and in a mouse MPTP model of PD, and neuroinflammation was investigated as a putative underlying mechanism. Viability assay on rat cortical neurons showed lack of cytotoxic effect in the dose-range of 100 nM–10 μM, which was therefore used for testing in vitro protection against H2 O2 and MPP+ neurotoxicity. MDG548 dose-dependently increased cell viability of rat cortical neurons co-treated with H2 O2 or pre-exposed to MDG548 prior to H2 O2 . Moreover, MDG548 induced neuroprotection in MPP+-treated PC12 cells. NF-kB activation was investigated to assess anti-inflammatory activity. MDG548 dose-dependently decreased NF-kB activation induced by LPS (100 ng/100 ml) in HEK-Blue-hTLR4 cells. Given the supposed cancer risk of other PPARγ agonists, Ames test for genotoxicity was performed in Salmonella typhimurium TA100 and TA98 strains, showing that MDG548 was not genotoxic. In vivo, BL/6J mice were treated with MPTP (20 mg/kg i.p. once/day for 4 days) in association with saline or MDG548 (2, 5, 10 mg/kg i.p.). Stereological counting showed that MDG548 prevented the MPTP-induced reduction in TH-positive cells in the substantia nigra compacta (SNc) at all doses tested. Moreover, MDG548 reduced reactive microglia and iNOS induction in the SNc. MDG548, being a non-TZD compound with high PPARγ affinity, void of genotoxicity, and with in vitro as well as in vivo neuroprotective properties, provides a promising alternative in the search for safer PPARγ agonists to be tested as potential disease-modifying drugs in PD.